Breaking the Divide: Can Public Spending on Social Infrastructure Boost Female Employment in Italy? - Jelena Reljic; Francesco Zezza (Global Labor Organization (GLO), 2024)
We contribute to the long-standing debate on the Italian North-South divide by assessing the impact of public spending on social infrastructure - including education, healthcare, childcare and social assistance - on the gender employment gap over the last two decades, using a PSVAR analysis. These investments, while not explicitly targeting women, may increase both their labour supply - by reducing the unpaid care work burden - and pro-women labour demand through job creation in care sectors that predominantly employ women. Our research reveals a positive and long-lasting impact of social infrastructure expenditure on private investment, GDP and employment in all areas of the country. However, the reduction of the gender employment gap is detected only in the South and among high-skilled women. These results stress the need for targeted policies to fill the investment gaps in social infrastructure, aiming for a more inclusive labour market, particularly in Southern regions, which suffer from chronic underinvestment and structural challenges.
Keywords: C33; E24; H30; J16; J18; J21; R58; 330; Social infrastructure; Gender inequality; Fiscal Policy; Panel SVAR; Italian regions